ACCEPTABLE LIMITS FOR CORRECTION OF HEATING LOAD WHILE OPTIMIZING OPERATIONAL MODES OF HEAT SOURCES - P. I. Diachek; V. A. Sednin; A. E. Zakharevich; I. V. Shkliar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Numerical investigations of temperature fields in the apartments of a multi-dwelling building has been carried out on the basis of the developed mathematical model and algorithm of its realization. The investigations have  made it possible to evaluate dynamics of changes in air temperature under unsteady conditions due to increase or reduction heating device capacity with regard to standardized values. The calculation results have demonstrated that a permissible period for capacity change accounts for not more than 6 hours. At the same time the rate of capacity change is up to 40 %. The obtained results can be practically used in the intelligent heating supply systems with the purpose to minimize consumption of fuel and power resources